Penguatan Personal Branding Dalam Rangka Persiapan Memasuki Dunia Kerja Bagi Mahasiwa Tingkat Akhir Di Kota Madiun - Afrisa Maya Adila Sary; Anggita Langgeng Wijaya (Pusat Riset dan Inovasi Nasional, 2023)
This community service activity aims to provide training related to personal branding to prepare for entering the world of work for final year students in Madiun. Personal branding and career preparation are essential, especially for final-year students who will soon graduate and enter the world of work. As a graduate who is a fresh graduate, of course, an introduction to the steps to enter the world of work and efforts to optimize personal branding as an effort to win competency in the world of work are fundamental needs. This activity was carried out for final-year students for several tertiary institutions in the City of Madiun, East Java. This community service activity was carried out twice, namely by online and offline methods, which were carried out at different times. The results of this community service activity showed an increase in the knowledge of the participants who participated in both online and offline activities, as seen from the increase in pre-test and post-test scores. This community service activity can be developed by increasing the number of activity participants and developing personal branding materials and interpersonal skills needed in the world of work. Training participants can also be developed, for example, with youth or orphanage youth who need knowledge about personal branding to enter the world of work.